The Influence Of Brand Image And Electronic Word Of Mouth On The Decision To Purchase Vivo Smartphones Among Students At Stie Ekuitas Bandung - Henny Utarsih; Muhammad Rizky Mubarokah Azis (CV Putra Publisher, 2026)
The rapid growth of the smartphone industry has intensified competition among smartphone brands, making it increasingly important for companies to understand the factors influencing consumers' purchasing decisions. This study aims to examine the influence of brand image and electronic word of mouth (eWOM) on the purchasing decisions of Vivo smartphones among students at STIE Ekuitas Bandung. This research employed a quantitative approach using a survey method. Primary data were collected through questionnaires distributed to 100 respondents selected from the student population. The data were analyzed using multiple linear regression to examine both the partial and simultaneous effects of the independent variables on purchasing decisions. The findings indicate that brand image has a positive and significant effect on purchasing decisions, suggesting that a favorable brand perception increases consumers' intention to purchase Vivo smartphones. In addition, electronic word of mouth (eWOM) also has a positive and significant influence, indicating that online reviews, recommendations, and user experiences shared through digital platforms play an important role in shaping consumer purchasing decisions. Simultaneously, brand image and eWOM significantly influence purchasing decisions, implying that both variables are essential components of an effective marketing strategy. The findings provide practical implications for smartphone companies, particularly Vivo, in strengthening brand image and optimizing digital word-of-mouth strategies to enhance consumer trust and purchase decisions.